2010
DOI: 10.1016/j.pain.2009.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex modulates placebo analgesia

Abstract: Expectations and beliefs modulate the experience of pain, which is particularly evident in placebo analgesia. The dorsolateral prefrontal cortex (DLPFC) has been associated with pain regulation and with the generation, maintenance and manipulation of cognitive representations, consistent with its role in expectation. In a heat-pain paradigm, we employed non-invasive low-frequency repetitive transcranial magnetic stimulation (rTMS) to transiently disrupt left and right DLPFC function or used the TMS device itse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
185
0
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 300 publications
(208 citation statements)
references
References 46 publications
9
185
0
14
Order By: Relevance
“…Our experimental approach clearly confirms this age effect. The difference scores between baseline and post-treatment in the analgesia-expectation group were 5.6-times higher than those found in a healthy adult population with regard to heat pain tolerance and 3.6-times higher with regard to heat pain threshold using a similar paradigm (12). Several psychological and neurodevelopmental reasons may account for the larger PR in children.…”
Section: Placebo Analgesia Responsesmentioning
confidence: 52%
See 1 more Smart Citation
“…Our experimental approach clearly confirms this age effect. The difference scores between baseline and post-treatment in the analgesia-expectation group were 5.6-times higher than those found in a healthy adult population with regard to heat pain tolerance and 3.6-times higher with regard to heat pain threshold using a similar paradigm (12). Several psychological and neurodevelopmental reasons may account for the larger PR in children.…”
Section: Placebo Analgesia Responsesmentioning
confidence: 52%
“…Clinical trials of local anesthetics (9,10) as well as a venipuncture study (11) emphasize the significance of PR in children. From a neurobiological perspective this is even more interesting since the prefrontal cortex (PFC) has repeatedly been implicated in the mediation of cognitive top-down expectation-related PR (12)(13)(14)(15) and given that this neural network undergoes considerable maturation during childhood (16,17). Surprisingly, to date there have been no experimental attempts to study PA in healthy children.…”
Section: Introductionmentioning
confidence: 99%
“…Previous PET studies suggested a major role of the DLPFC in controlling pain perception by modulation of cortico-subcortical and cortico-cortical pathways [29]. In addition, several studies have highlighted the potential role of the DLPFC in placebo analgesia [30][31][32] and pain catastrophizing [33]. In a brain chemistry study of patients suffering from chronic back pain using in vivo single-voxel proton magnetic resonance spectroscopy ( 1 H-MRS), Grachev and colleagues [9] were able to demonstrate a depletion of N-acetyl aspartate and glucose within the DLPFC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, direct evidence has been supplied that fMRI responses related to painful heat stimulation can be reduced in the ipsilateral dorsal horn under placebo analgesia [28]. Also of note, permanent [29] or transitory [30] impairment of prefrontal cognitive functions results in the disruption of placebo analgesia.…”
Section: Three Neurotransmitters Have Been Identified In Placebo Analmentioning
confidence: 99%